Transregional astrocyte-dependent metaplasticity in the hippocampus - Shruthi Sateesh; Barbara J. Logan; Miki Suzuki; David Stellwagen; Wickliffe C. Abraham (Proceedings of the National Academy of Sciences, 2026)
Learning-related synaptic plasticity is regulated by metaplasticity, which adjusts plasticity thresholds in an activity-dependent manner. We have previously described a heterodendritic form of metaplasticity whereby priming stimulation in stratum oriens (SO) inhibits subsequent long-term potentiation (LTP) in the neighboring stratum radiatum of the hippocampal CA1 region. Here, we report that this metaplasticity is transregional, in that the SO priming stimulation also inhibits later LTP induction at dentate gyrus (DG) middle molecular layer (MML) synapses, both in vitro and in vivo. This effect operates across the hippocampal fissure and occurs in the absence of CA3, highlighting a previously unappreciated reverse-direction and long-distance hippocampal crosstalk. Our findings demonstrate an essential role of astrocytes as SO priming elicited an increase in the frequency of calcium (Ca 2+ ) events in astrocytes in the DG MML, while the metaplasticity effect was blocked by calcium-buffering in MML astrocytes. It could be triggered by either activation of M1 muscarinic acetylcholine receptors or group II metabotropic glutamate receptors, and was critically dependent on inositol 1,4,5-trisphosphate receptor type 2 signaling. The transregional inhibition of LTP was mediated by astrocytic release of tumor necrosis factor (TNF), which likely acts in an autocrine fashion on astrocytic TNF type 1 receptors (TNFR1s). Downstream of TNF-TNFR1 signaling, the inhibition of MML LTP was mediated by the activation of GluN2B-containing N-methyl-D-aspartate receptors. Thus, a complex, bidirectional neuron–glia signaling cascade orchestrates long-distance metaplasticity across hippocampal subregions, providing a framework for understanding how hippocampal neuronal networks dynamically regulate plasticity thresholds across space and time.